ANALISIS VOLUME TIMBUNAN SEDIMEN KOLAM RETENSI RUMAH SAKIT ISLAM SITI KHADIJAH PALEMBANG - Reni Andayani; Rosmalinda Permatasari; M Nur Ilham; Okma Yendri (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Palembang City, especially the Demang Lebar Daun Sub-district area which every year during the rainy season always experiences flooding caused by the topography in the form of lowlands so that during the rainy season it receives a large amount of water flow. The retention pond of the Siti Khadijah Hospital on Jalan Demang Lebar Daun is a retention pond that is able to accommodate excess water in the area, but this pond is no longer able to overcome the problem of flooding, one of the causes being the capacity of the existing retention pond that is not appropriate and the problem of sedimentation deposits. The research method used was a measurement survey to obtain data on the cross-sectional area and depth of the pond, in addition to taking sediment samples at the inlet, outlet and middle of the pond to carry out filter analysis and specific gravity in the laboratory. The results of the study showed that based on sediment analysis using the Frijlink method, the largest basic sediment discharge was 5.192 x 10-6 m3/s/m, the basic sediment volume (bed load) was 3.7832 x 10-6 m3/s and the largest retention pond embankment volume was 25,788.25 m3/year.